(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Agriculture is the primary source of livelihood for about 60% of Indian population. Indian agriculture needs set of solutions for improvisation of both the farmers and the agricultural land. Agriculture contributes only 16% GDP for the country but it is the largest sector for employment. Apart from economy, Indian agriculture needs sustainable, efficient, technical and mainly productive farming. In this project, Paddy is taken as the field to be improvised. Paddy is categorized as 3 different varieties. Using the basic parameters of an agricultural land has membership function inputs such as temperature, humidity, sunlight and soil moisture, the respective membership outputs viz., water irrigation, plant growth and plant diseases are to be found. Membership functions come under the concept of fuzzy logic. Fuzzy logic basically uses membership functions to determine outputs for all calculations. Using IR cameras, plant growth can be easily monitored and analysed. Using this technique, basic necessities of an agricultural land can be satisfied and is also useful for productive farming. The main concentration of this idea is based on the cultivation of three different varieties of paddy.